Large volume "mammotome" biopsy may reduce the need for diagnostic surgery in papillary lesions of the breast. Issue 8 (21st May 2008) - Carder, P J; Khan, T; Burrows, P; Sharma, N
Abstract : Background: There is currently debate as to whether all papillary lesions diagnosed on breast needle core biopsy (BNCB) require surgical excision. The development of large volume "mammotome" biopsy now permits non-operative removal. Few studies have assessed the usefulness of this approach. Aim: To review the pathological and radiological findings in a series of B3 and B4 papillary lesions identified on conventional BNCB with a view to assessing the usefulness of mammotome biopsy as a means of avoiding diagnostic surgery. Methods: All BNCBs from 23 June 2005 to 14 August 2007 that contained a B3 or B4 papillary lesion were identified by searching the pathology department records. Follow-up histology and radiological details were obtained. Results: 34 papillary BNCBs were included in this study: 21 from screen-detected lesions and 13 from patients presenting symptomatically. 31 were classified B3 and three were B4. Four cases included an atypical ductal epithelial proliferation (three B4, one B3). 14 patients had undergone open surgical biopsy, 15 had undergone mammotome excision, and five had had no subsequent procedure. All cases that had undergone mammotome biopsy had not shown atypia on the core, and 13 (87%) proved benign. In two cases the mammotome biopsy was either atypical or malignant, prompting surgery; the biopsy changes deriving from areas of ductal carcinoma in situ arising in the context of multiple intraduct papillomas and both were distinctive mammographically in presenting with large areas of segmental calcification. 11/14 cases that had undergone surgical excision had not shown atypia on the core, and proved benign. All three cases with atypia on the core proved malignant. Conclusion: In selected cases, mammotome biopsy may improve sampling of papillary lesions such that malignancy may be excluded without recourse to diagnostic surgery. Mammotome in such cases effectively acts as a therapeutic procedure. This has important implications for symptomatic and breast screening services.